Optimizing the architecture of lung-inspired fuel cells. (6th April 2020) - Cho, J.I.S.; Marquis, J.; Trogadas, P.; Neville, T.P.; Brett, D.J.L.; Coppens, M.-O.
Highlights: Simulations of a lung-inspired polymer electrolyte membrane fuel cell are presented. The optimal number of generations corresponds to transition from flow to diffusion. The effect of GDL thickness on the lung-inspired PEMFC performance is investigated. The potential for 80% increase in PEMFC volumetric power density is demonstrated. Abstract: A finite-element model of a polymer electrolyte membrane fuel cell (PEMFC) with fractal branching, lung-inspired flow-field is presented. The effect of the number of branching generations N on the thickness of the gas diffusion layer (GDL) and fuel cell performance is determined. Introduction of a fractal flow-field to homogenize reactant concentration at the flow-field | GDL interface allows for the use of thinner GDLs. The model is coupled with an optimized cathode catalyst layer microstructure with respect to platinum utilization and power density, revealing that the 2020 DoE target of ~8 kW/gPt is met at N  = 4 generations, and a platinum utilization of ~36 kW/gPt is achieved at N  = 6 generations. In terms of the overall fuel cell stack architecture, our results indicate that either the platinum loading or the number of cells in the stack can be reduced by ~75%, the latter option of which, when combined with a 100 µm GDL, can lead to >80% increase in the volumetric power density of the fuel cell stack.